(untitled) (Desarrollo, Estado y Espacio, 2022)
"State space" is a tool of ideological critique through which it is intended to overcome the understanding of space based on statistical empiricism and the formalism of static jurisdictions. State territoriality was discussed from different theoretical approaches such as the disjunctive between politics of scale and scale as politics, the contingency between structural forces and actors’ practices, and the corporealization of space from a relational logic, among others. In the Latin American context, however, the problematization of state space –and in general of the spatial dimension– is usually considered tacitly, rather than in an explanatory way. In this special issue of RDEE, we propose to resume the discussion on the production of state space, providing a Latin American perspective and problematizing, in particular, the ways in which the state attempts to mediate by creating new spaces to respond to the economic conditions imposed by the new framework of global competition and, at the same time, the way in which the state reconfigures itself in this endogenous and exogenous process.